The exceptionally, extraordinarily ordinary first day of school - Lorenz, Albert, 1941- (Abrams Books for Young Readers, 2010)
On his first day at a new school, John answers the librarian's questions about what his former school was like, concocting a wild story of attending classes in a castle, where the lunch menu includes worms and storybook characters come to life.